An Analysis of the Planar Vault under the Choir Loft of the Monastery of El Escorial - Rubén Rodríguez Elizalde (Buildings, 2024)
Arches and vaults are typical elements of ancient buildings. They are formed by voussoirs that resist the pressure they receive and transmit them through compression forces. The transmission of these forces justifies their curved shape. For this reason, arches and vaults are omnipresent elements in ancient constructions, all of them masonry structures. However, when visitors enter the Basilica of the Monastery of El Escorial, they find a narthex with a flat or planar vault. This vault is located under the floor of the choir loft. Its geometric characteristics and its shape, with no curvature, make it an architectural anomaly and a brilliant solution within masonry structures. Therefore, this article tries to analyse the construction process and structural behaviour of this vault, to understand its operation and how it remains standing five hundred years after its construction.